2014
DOI: 10.5935/0034-7167.20140050
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic profile of smokers admitted to the psychiatric ward of a general hospital

Abstract: A partir do interesse dos profissionais da saúde em controlar o tabagismo, chamou a atenção sua elevada frequência na população psiquiátrica. Neste estudo, objetivou-se identificar o perfil sociodemográfico de pacientes psiquiátricos, tabagistas, comparando-o com o de ex-tabagistas e não tabagistas. Pesquisa exploratória, realizada de agosto de 2010 a fevereiro de 2012, envolvendo pacientes psiquiátricos, internados em hospital geral, por meio de entrevista com questionário estruturado. Das 433 pessoas interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…The age of smoking initiation had an average of 16.9 ± 4.8 years, with a minimum age of eight years. National studies (11,16) have presented similar results. According to research (17) in 2011, 17-19 years was the predominant age group for the initiation to regular consumption of tobacco products.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The age of smoking initiation had an average of 16.9 ± 4.8 years, with a minimum age of eight years. National studies (11,16) have presented similar results. According to research (17) in 2011, 17-19 years was the predominant age group for the initiation to regular consumption of tobacco products.…”
Section: Discussionsupporting
confidence: 66%
“…The prevalence of smoking among those responsible for tobacco production was 17%, with an average of 29.3 ± 14.5 years of consumption. Studies (11,16) with similar populations showed variations in smoking prevalence from 10% to 23.5%. The prevalence of smoking found in this investigation is higher than the national average (4) and close to the percentage of 20.4% prevalence in rural areas, as published by Special Survey of Tobacco Use (17) .…”
Section: Discussionmentioning
confidence: 85%
“…In the present study, the female gender predominated (66%), a profile similar to that found in the literature (CARAM, 2009;BORTOLUZZI, 2011;Campos et al, 2014) and different from the study by Oliveira et al (2014 ), in which the male gender predominated. A difference that seems to be explained by the specificity of the condition of the study population, apparently more related to the male sex (OLI-VEIRA, 2014).…”
Section: Discussionsupporting
confidence: 85%